2021
DOI: 10.2147/idr.s289763
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Detection of Carbapenem-Resistant Gram-Negative Bacilli from a Clinical Specimen in Sidama, Ethiopia: A Cross-Sectional Study

Abstract: Background Carbapenem-resistant gram-negative bacteria are an emergent source of both community-acquired and healthcare-associated infection that poses a substantial hazard to public health. This study aimed to conclude the magnitude of carbapenem resistance gram-negative bacteria from a clinical specimen at Hawassa University Comprehensive Specialized Hospital. Methods A hospital-based cross-sectional study was accompanied from February 13 to June 7, 2020, in which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
(60 reference statements)
3
6
2
1
Order By: Relevance
“…In our study, the prevalence of carbapenemase-producing gram-negative bacilli was 5.4%, which is higher than the prevalence of study conducted at the University of Gondar, Ethiopia by Eshetie et al at 2.72% [ 41 ] and the Ethiopian Public health Institute by Beyene et al at 2% [ 37 ]. However, our result was lower than the result of studies conducted at Tikur Anbessa Specialized Hospital, Ethiopia by Melese et al with 12.12% [ 42 ], Three Hospitals in Amhara region, Ethiopia by Moges et al 15.7% [ 43 ], Felegehiwot Hospital, Ethiopia by Moges et al 16.2% [ 44 ], Sidama, Ethiopia by Alemayehu et al 9% [ 45 ], Mulago National Referral Hospital, Uganda by Okoche et al 22.4% [ 46 ], and data from laboratories in Spain by Lopez-Hernandez et al 62% [ 47 ]. The variation might be due to the method utilized, i.e.…”
Section: Discussioncontrasting
confidence: 72%
“…In our study, the prevalence of carbapenemase-producing gram-negative bacilli was 5.4%, which is higher than the prevalence of study conducted at the University of Gondar, Ethiopia by Eshetie et al at 2.72% [ 41 ] and the Ethiopian Public health Institute by Beyene et al at 2% [ 37 ]. However, our result was lower than the result of studies conducted at Tikur Anbessa Specialized Hospital, Ethiopia by Melese et al with 12.12% [ 42 ], Three Hospitals in Amhara region, Ethiopia by Moges et al 15.7% [ 43 ], Felegehiwot Hospital, Ethiopia by Moges et al 16.2% [ 44 ], Sidama, Ethiopia by Alemayehu et al 9% [ 45 ], Mulago National Referral Hospital, Uganda by Okoche et al 22.4% [ 46 ], and data from laboratories in Spain by Lopez-Hernandez et al 62% [ 47 ]. The variation might be due to the method utilized, i.e.…”
Section: Discussioncontrasting
confidence: 72%
“…In this retrospective study, we analyzed the five-year antimicrobial resistance profiles of P. aeruginosa and Acinetobacter species with an emphasis on the prevalence and trends of carbapenem resistance at the Ethiopian Public Health Institute, Addis Ababa, Ethiopia. The prevalence of carbapenem-resistant Acinetobacter species in the current study was 61%, which is consistent with the findings of the study from Pretoria, South Africa (63%), 27 and Jimma, Ethiopia (56.4%), 25 however, it is higher than the findings of studies from Lusaka, Zambia (18.2%), 28 Switzerland (9.2%), 29 North-East, Ethiopia (34.5%), 18 Sidama, Ethiopia (9.9%), 22 North Gondar, Ethiopia (20.77%), 24 Northwest Ethiopia (33.3%), 17 and Dessie, Ethiopia (43.8). 16 The variation could be attributed to differences in study design, the number of isolates analyzed, the types of specimens considered, and the amount of data analyzed, as some studies only analyzed fewer data, while others analyzed a large amount of national antimicrobial resistance data, geographical differences, and antibiotic prescription policy differences.…”
Section: Discussionsupporting
confidence: 91%
“…During the study period, Acinetobacter species demonstrated the highest resistance to piperacillin/tazobactam (85.5%), extended-spectrum cephalosporins (ceftazidime 94.6%, ceftriaxone 94.1%, and cefepime 90%) and lowest resistance to aminoglycosides (amikacin 31.5%, and tobramycin 51.7%) and carbapenems (imipenem 59%) Table 2. Although the prevalence of resistance is higher in our study, the result is partially in agreement with studies from Sidama, Ethiopia, 22 and Northeast Ethiopia, 16,18 which reported the highest resistance to extended-spectrum cephalosporins and piperacillin/ tazobactam and lowest resistance to aminoglycosides and carbapenems.…”
Section: Overall Antimicrobial Resistancesupporting
confidence: 92%
See 1 more Smart Citation
“…Ethiopia by Moges et al15.7%[25], Felegehiwot Hospital, Ethiopia by Moges et al 16.2%[26], Sidama, Ethiopia by Alemayehu et al 9%[27], Mulago National Referral Hospital, Uganda by Okoche et al 22.4%[28], and data from laboratories in Spain by Lopez-Hernandez et al 62%[29]. The variation might be due to the technique utilized, modified carbapenem inactivation method was utilized in our investigation unlike other investigators who used the modified Hodge test, the number of bacterial isolates analyzed, geographic location.…”
mentioning
confidence: 99%